Bcl-xL/Bak interaction and regulation by miRNA let-7b in the intrinsic apoptotic pathway of stored platelets. (2nd January 2019) - Yan, Yuzhong; Xie, Rufeng; Zhang, Qi; Zhu, Xinfang; Han, Jia; Xia, Rong
Abstract: Bcl-2 family proteins play key roles in the intrinsic apoptosis pathway in platelets, with both pro- and antiapoptotic protein expressions regulating survival during ex vivo storage. We detected a significant decrease in antiapoptotic Bcl-xL and increase in proapoptotic Bak expression on the third day of storage and as a result the ratio of Bak:Bcl-xL also decreased. Moreover, we identified an interaction between Bcl-xL and Bak. These shifts corresponded with activation of the apoptotic pathway, suggesting these proteins might play an important role in platelet survival. We then performed bioinformatic analysis to gain insight into protein expression regulation during storage. This identified a potential binding site of the microRNA (miRNA) let-7b in the 3ʹ-UTR of the Bcl-xL gene, which we confirmed by a dual-luciferase reporter assay. We also determined that let-7b was upregulated during platelet storage, and let-7b transfection influenced Bcl-xL and Bak protein, but not mRNA, expression. Together, these data suggest that only posttranscriptional mechanisms are available for regulating gene expression in anucleate platelets.